Motivational Non-directive Resonance Breathing as a Treatment for Chronic Widespread Pain - Paccione, Charles Ethan; Jacobsen, Henrik Børsting (Frontiers in Psychology, 2019)
Chronic widespread pain is one of the most difficult pain conditions to treat due to an unknown etiology and a lack of innovative treatment design and effectiveness. Based upon preliminary findings within the fields of motivational psychology, integrative neuroscience, diaphragmatic breathing, and vagal nerve stimulation, we propose a new treatment intervention, motivational nondirective resonance breathing, as a means of reducing pain and suffering in patients with chronic widespread pain. Motivational nondirective resonance breathing provides patients with a noninvasive means of potentially modulating five psychophysiological mechanisms imperative for endogenously treating pain and increasing overall quality of life.